SIFAT MEKANIKA KAYU KEMIRI (Aleurites mollucana Willd) ASAL SULAWESI TENGAH BERDASARKAN ARAH AKSIAL - Sari, Nurmala; Erniwati, Erniwati; Hapid, Abdul (Universitas Tadulako, 2015)
Until present day, using wood species is extremely limited while there are thousands of ignorance species. A lot of research results indicated that woods of lesser known species propose some very good properties as raw materials of wood industry where one of them is candlenut wood. The objective of the research was to know the mechanical properties of the wood referring its axial position (base, middle and top of the trunk). The mechanical properties consist of the comprehensive strength parallel to the grain, modulus of rapture (MOR) and modulus of elasticity (MOE). The benefit of the research is as an useful information for Perhutani in industrial processing of the candlenut wood. The research used a candlenut tree with 39 cm of diameter and 20 m of hight, than 10 years old originating from Ranteleda village, Palolo sub district, Sigi district. Establishment of examined sample used Germani Standard (DIN). By using Completely Randomized Design as a method of experimental design, the research decided the differences on the axial positions (base, middle, and top) as the treatments. The results show the values of the comprehensive strength parallel to the grain are 27,96 N/mm2, 19,51 N/mm2, and 17,51 N/mm2. MOE are 4666,01 N/mm2, 4616,19 N/mm2, and 4295,83 N/mm2. Meanwhile MOR are 65,59 N/mm2, 64,69 N/mm2, 59,40 N/mm2. The axial positions don’t significantly influence the mechanical properties: the comprehensive strength parallel to the grain, modulus of rapture, and modulus of elasticity Keywords: strength parallel to the grain, modulus of rapture (MOR) and modulus of elasticity (MOE), candlenut.